Luis Loayza y el canon de la literatura peruana: condición colonial, ética literaria y forma ensayística en El sol de Lima. - CASTAÑEDA, LUIS H. (Revista Hispánica Moderna (0034-9593), 2014)
This article presents a literary criticism for the book "El sol de Lima," written by Luis Loayza. The author comments on the narrative structure of the work, which is presented in 20 essays. He also considers the elements of irony and symbolism throughout the work. The book's placement among the Peruvian literary canon is also explored.